2015
DOI: 10.14720/aas.2015.105.2.03
|View full text |Cite
|
Sign up to set email alerts
|

Sonication of seeds increase germination performance of sesame under low temperature stress

Abstract: A laboratory experiment was conducted to determine the effect of ultrasound (US) exposure time on germination behavior of sesame seeds. All tests were carried out at 20 kHz in a water bath ultrasonic device varying two factors, treatment duration (10, 20 and 30 min) and germination temperature (15, 20 and 25 ºC). Parallel tests were run in which seeds were soaked in water without sonication in order to eliminate the effect of water from US test results. US treatments enhanced seeds water uptake. At mild exposu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
14
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 23 publications
2
14
0
3
Order By: Relevance
“…Se ha reportado que el uso de CM intensos (>1 mT, miliTesla) mejora el vigor en semillas (Yaldagard, 2008;Hołubowicz et al, 2014;Baser-Kouchebagh, 2014;Shekari, 2015;Bose et al, 2018). En general, se ha observado un incremento en la tasa de germinación en semillas de especies importantes para la agricultura manteniéndose estos efectos vigorizantes durante el ciclo del cultivo (Wyjcik, 1995;Nedialkov et al, 1996;De Souza et al, 1999;Carbonell et al, 2000;Aladjadjiyan, 2002;Soltani et al, 2006;Flórez et al, 2007;Poinapen et al, 2013).…”
Section: Campo Magnético (Cm) Como Acondicionador Físico De Semillasunclassified
“…Se ha reportado que el uso de CM intensos (>1 mT, miliTesla) mejora el vigor en semillas (Yaldagard, 2008;Hołubowicz et al, 2014;Baser-Kouchebagh, 2014;Shekari, 2015;Bose et al, 2018). En general, se ha observado un incremento en la tasa de germinación en semillas de especies importantes para la agricultura manteniéndose estos efectos vigorizantes durante el ciclo del cultivo (Wyjcik, 1995;Nedialkov et al, 1996;De Souza et al, 1999;Carbonell et al, 2000;Aladjadjiyan, 2002;Soltani et al, 2006;Flórez et al, 2007;Poinapen et al, 2013).…”
Section: Campo Magnético (Cm) Como Acondicionador Físico De Semillasunclassified
“…Successful results have been obtained from the studies on the effect of ultra-sonic sound applications on seed germination and plant growth. It has been reported that Ultra-sonic sound application induces seed germination (Creath and Schwartz 2004;Wang et al, 2012;Miano et al, 2015;Shekari et al, 2015;Liu et al, 2016;López-Ribera and Vicient, 2017). It has been stated that Ultra-sonic sound vibrations have effects such as washing the germination inhibitory substances in the seed coat, increasing in the embryonic development of the vibrations, and thinning the impermeable layer on the outer part of the seed coat (Gaba et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…It also increases in germination percentage, root and stem length of seedlings, and seedling emergence index. It promotes enzyme activity and initiation of other biological processes (Baker et al, 2001;Teixeira Da Silva and Dobránszki, 2014;Shekari et al, 2015). In addition, this technique provides seed application by modifying the seed coat without damaging the seed, with natural drying allowing storage after application (Porto et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Water is a key driver of agricultural production in the world and provides more than a quarter of the total world cereal output (Shekari et al, 2015;Mursalova et al, 2015). In the past four decades, annual cereal production increased 3.8-fold from 100 million tones in 1961 to 410 million tones in 2004 (FAO, 2005).…”
Section: Introductionmentioning
confidence: 99%